To own or not to own? Car ownership and consumer awareness: Evidence from an Italian survey. (December 2019) - Burlando, Claudia; Ivaldi, Enrico; Parra Saiani, Paolo; Penco, Lara
Abstract: This paper has two objectives. First, the paper aims to advance knowledge on factors that lead to the choice of car sharing, by proposing, for the first time a different perspective based upon the attitude towards the use of private car. Second, the study helps to understand the connection between the rate of penetration of car sharing services and the attitude towards the use of the private car, analysing also the socio-demographic influences on car-sharing behaviour. The paper draws on the findings from a telephone-structured questionnaire we carried out in this under-explored market area in four urban metropolitan cities in Italy (Rome, Milan, Turin and Genoa). For this purpose, we firstly made an exploratory factor analysis to determine the key dimensions of private car behaviour. We then performed a logistic regression model in order to analyse which factors may affect the dependent variable.